Pengaruh gamifikasi terhadap perceived enjoyment pada mata pelajaran ipas sekolah dasar gugus II ahmad yani kecamatan laweyan - Fitriya Handayani; Roy Ardiansyah (Universitas Sebelas Maret, 2025)
This study aims to examine the impact of gamification on students' perceived enjoyment in Natural and Social Sciences (IPAS) at elementary schools in the Ahmad Yani Cluster, Laweyan District. This study was motivated by the observation that students often find the learning of IPAS less interesting, which leads to low perceived enjoyment. This study used a quantitative quasi-experimental approach involving fourth-grade students. SDN Dukuhan Kerten served as the experimental group, while SDN Tegalrejo served as the control group. To measure students' perceived enjoyment, data were collected through a questionnaire. Our findings indicate a significant positive effect between gamification and perceived enjoyment. The calculated t-value exceeds the table t-value, so the null hypothesis is rejected. In addition, the N-Gain test showed an increase in the experimental class, while the control class remained in the low category. In conclusion, this study shows that gamification is effective in increasing students' perceived enjoyment. This also has practical implications, encouraging educators to use this approach. The implementation of gamification can increase students' motivation, engagement, and perceived enjoyment in IPAS.